2016
DOI: 10.7150/thno.16425
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Targeting Based Delivery of Therapeutic Peptide using AP1-ELP Carrier for Effective Cancer Therapy

Abstract: Elastin-like polypeptide (ELP)-based drug delivery has been utilized for various applications including cancer therapies for many years. Genetic incorporation of internalization ligands and cell-targeting peptides along with ELP polymer enhanced tumor accumulation and retention time as well as stability and activities of the drug conjugates. Herein, we described a unique delivery system comprised of genetically engineered ELP incorporated with multiple copies of IL-4 receptor targeting peptide (AP1) periodical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…Previously, we reported that [AP1-V12]6, ELP-based polymer consisting of six repeats of AP1 increased binding avidity and affinity towards IL-4R. The polymer was highly localized to IL-4R-expressing tumor tissue after intravenous injection and was retained up to 24 h. Moreover, [AP1-V12]6 showed higher accumulation in the liver and kidney, which may be attributed to its lower molecular weight [34,35]. Thus, various multivalentbased AP1-ELP polypeptides containing random repetitions of IL-4R-targeting peptide with different molecular weights were generated.…”
Section: Ivyspringmentioning
confidence: 98%
See 2 more Smart Citations
“…Previously, we reported that [AP1-V12]6, ELP-based polymer consisting of six repeats of AP1 increased binding avidity and affinity towards IL-4R. The polymer was highly localized to IL-4R-expressing tumor tissue after intravenous injection and was retained up to 24 h. Moreover, [AP1-V12]6 showed higher accumulation in the liver and kidney, which may be attributed to its lower molecular weight [34,35]. Thus, various multivalentbased AP1-ELP polypeptides containing random repetitions of IL-4R-targeting peptide with different molecular weights were generated.…”
Section: Ivyspringmentioning
confidence: 98%
“…Protein samples were diluted to 25 μM in PBS and filtered through a 0.2-μm Whatman syringe filter (GE Healthcare, Amersham, UK) to remove impurities. The CD spectra were measured at the different temperatures of 20,25,30,35,40,50, and 60 °C in a 0.1-cm path length cell. The spectra were recorded from 180 to 260 nm at a scan speed of 50 nm/min.…”
Section: Circular Dichroism Spectra (Cd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these new chimeric AP1-ELP-KLAK NPs enhanced tumor accumulation and retention time, thus making them promising candidates for effective cancer therapy. Due to the simple preparative procedures of these ELRs, this platform could also be used as a good carrier for tumor-specific delivery of other therapeutic agents [54].…”
Section: Nanoparticles From Hybrid Elrsmentioning
confidence: 99%
“…Therefore, IL-4R-based tumor targeting drug delivery could be used for the treatment of several tumors. CRKRLDRNC peptide (AP1 peptide), selected through the phage-display technology, was reported to selectively bind to IL-4R [ 28 ]. Herein, we developed DOX-loaded nanoparticles and decorated on its surface with AP1 peptide for both glioma cells and angiogenesis dual targeting delivery of doxorubicin.…”
Section: Introductionmentioning
confidence: 99%